Modern University in the Light of Lifelong Learning Challenges: The Issues of Philosophy of Education - Semeniuk, Natalia (Studia Warmińskie, 2019)
The philosophical analysis of the content of the modern university's work leads to an understanding of commercialization and professional localization in the training of specialists. The ways of determining the essence of a modern university are grounded: elite, mass, niche, regional, pragmatic, ecological, and others. It is argued that the commercialization of education is conditioned by an increase in the level of technology impact on the dynamics of cultural development, globalization and informatization of society. Accordingly, traditional notions of academic freedom and the value of science and education are inferior to considerations of pragmatic feasibility and utilitarianism. The idea of ​​the perniciousness of such a trend in education that threatens the personality deformation and the possible risks of global catastrophes is upheld in the paper.